Pengelolaan Sampah Plastik di Desa Layeni Kecamatan TNS Kabupaten Maluku Tengah - La Ode Angga; Sabri Fataruba; Ronald Fadly Sopamena; Danillo O Saununu (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Outreach to the community with the title Plastic Waste Management in Layeni Village, TNS District, Central Maluku Regency.Purposes of Devotion: Provide understanding to the community regarding plastic waste management and it is hoped that the people of Layeni Village, TNS District, Central Maluku Regency can carry out waste management in an effective, integrated and sustainable manner.Method of Devotion: Performed with the lecture method by each of the presenters. The lecturer is given time to deliver the material, after which the participants are invited to ask a problem or question, which is then answered in turn by the speaker according to the problem being asked.Results of the Devotion: This community service activity is a form of tridarma activity for educators to play a role in solving problems that occur in the community, especially regarding the management of plastic waste. Through community service by conducting counseling on this plastic waste management, the community will know good, integrated, effective and sustainable waste management.